G160 Establishing a specialist clinic for children with fasd. (12th March 2018) - Bond, M; Bennett, S; Aiton, N
Abstract : Aim: To establish a specialist clinic to streamline the diagnosis of children suspected of having FASD (Fetal Alcohol Spectrum Disorders). Method: There are several tools available for assessing children with FASD. The 4-digit code was chosen (Astley SJ et al), for a number of reasons including: comprehensive nature, the ability to express uncertainty, availability of photographic facial assessment. Photography was included as part of the assessment and a clinical photographer attended the clinic. The photographs were analysed using computerised analysis (fasdpn.org). Criteria: children were accepted for referral from the One Stop Clinic – a clinic in Brighton for pregnant mothers with substance misuse, or when there was concern that a child's problems might be related to prenatal alcohol exposure. Results: 20 children were assessed in the first year. 8 children were diagnosed as having FASD. Other problems related to conditions such as attachment difficulties, ADHD and learning disability. There were a small number of children where prenatal alcohol exposure was suspected but unknown, particularly following adoption. Some children are still awaiting psychological assessment (due to maternity leave) before a diagnosis can be ascribed. Conclusion: It was possible to build in a specialist clinic without significant extra resources. Additional resources required were a) software required for the facial analysis, and b) training in the use of the 4-digit code (available as an on-line module) As the clinic developed, an increasing part of the clinic time was taken up with multidisciplinary discussion in 2 areas: what information was available at the time of referral, and what further information/assessments would be required which would be helpful in reaching a diagnosis, and in reaching consensus regarding the final diagnosis. Informal feedback from teachers, social workers and carers has shown that they have found the clinic helpful and valuable. (formal feedback in progress). The presence of a specific clinic dedicated to FASD helped provide a focus for referral concerns, develop and concentrate expertise among professionals, and allow ongoing collection of appropriate data.